Obrzędowość rodzinna utrwalona we frazemach gwarowych pogranicza małopolsko-mazowieckiego - Paulina Karpeta (Annales Universitatis Paedagogicae Cracoviensis. Studia Linguistica, 2022)
The article is a review of family beliefs and habits embedded in dialect phrases that the author collected in several villages on the Lesser Poland-Masovian borderland. Such an approach to the subject comprehensively shows the cultural and moral sphere of a given community and preserves its specificity. As a rule organizing the material base, the author adopted the method of thematic fields, which will allow to distinguish conceptual categories typical of the rural linguistic and cultural community. Research on old customs and folk rituals – taking into account socio-economic transformations – is a bridge connecting the present with the past.